2022
DOI: 10.1002/htj.22626
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion‐thermo effect on MHD dissipative flow past a porous vertical plate through porous media

Abstract: In this study, we investigate the heat and mass transfer in MHD convective flow past an infinite plate, through a porous media in presence of radiation, diffusion-thermo effect, and heat sink. A uniform magnetic field is applied transversely in the fluid region. The novelty of the present work is to analyze the diffusion-thermo effect on the flow phenomena in the presence of heat sink and thermal radiation. The governing equations are solved by perturbation technique to get expressions for velocity, temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
1
14
0
1
Order By: Relevance
“…Magnetic field Continuity equation 1 : true·trueB=0. $\overrightarrow{\nabla }\cdot \overrightarrow{B}=0.$…”
Section: Mathematical Formulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Magnetic field Continuity equation 1 : true·trueB=0. $\overrightarrow{\nabla }\cdot \overrightarrow{B}=0.$…”
Section: Mathematical Formulationmentioning
confidence: 99%
“…Ohm's law 1 : trueJ=(E+q×B)σ. $\overrightarrow{J}=(\overrightarrow{E}+\overrightarrow{q}\times \overrightarrow{B})\sigma .$…”
Section: Mathematical Formulationunclassified
See 2 more Smart Citations
“…They are also known to change the way flow behaves at boundary layers. The fluid flows through a cone in a porous medium has been studied earlier by Mehta et al, 28 Choudhury et al, 29 and Usman et al 30 The bivariate Chebyshev spectral collocation quasilinearization method (BSQLM) to solve the existing equations of mixed convection flow via cone in porous media was reported by Ilya et al 31 Ahmad et al 32 investigated the influence of porous media on the MHD micropolar fluid via a cone and they found that the increasing porous parameter values, decreased the flow of micro rotation. The behavior of the heat and mass transfer in MHD Casson fluid flow past a cone in porous media with gyrotactic microorganisms was studied in Iqbal et al 33 The effect of Heat as well as mass transfer on unsteady convective MHD Couttee flow via a porous medium with varying temperature was analyzed in Sasikumar 34…”
Section: Introductionmentioning
confidence: 98%